2002
DOI: 10.1007/s00454-002-0735-x
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of Real Wronski Maps

Abstract: We study the map which sends vectors of polynomials into their Wronski determinants. This defines a projection map of a Grassmann variety which we call a Wronski map. Our main result is computation of degrees of the real Wronski maps. Connections with real algebraic geometry and control theory are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 18 publications
2
73
0
Order By: Relevance
“…The conjecture is proved in [EG02b] for r D 1; see a more elementary proof also for r D 1 in [EG05]. The conjecture, its supporting evidence, and applications are discussed in [EG02b], [EG02a], [EG05], [EGSV06], [ESS06], [KS03], [RSSS06], [Sot97a], [Sot97b], [Sot99], [Sot00b], [Sot03], [Sot00a] and [Ver00].…”
mentioning
confidence: 99%
“…The conjecture is proved in [EG02b] for r D 1; see a more elementary proof also for r D 1 in [EG05]. The conjecture, its supporting evidence, and applications are discussed in [EG02b], [EG02a], [EG05], [EGSV06], [ESS06], [KS03], [RSSS06], [Sot97a], [Sot97b], [Sot99], [Sot00b], [Sot03], [Sot00a] and [Ver00].…”
mentioning
confidence: 99%
“…The most promising approach to this conjecture seems to be the study of the geometry of the Wronski map from Grassmannians to projective spaces, see e.g. [EG2]. Namely, consider the map W k,n : G k+1,n+1 → RP (k+1)(n−k) associating to a (k + 1)-dimensional linear subspace in the space of polynomials its Wronskian, i.e.…”
Section: Explanations Tomentioning
confidence: 99%
“…Eremenko and Gabrielov [3] showed that the number of real solutions to certain systems of real polynomial equations is bounded below by the topological degree of the corresponding Wronski map, and computed this degree. Soprunova and Sottile [19] extended the definition of the real Wronski map to certain sparse polynomial systems associated with partially ordered sets, computed its degree and derived the corresponding lower bounds on the number of real solutions.…”
Section: Introductionmentioning
confidence: 99%